(untitled) (Research, Society and Development, 2022)
Objective: to describe the deaths of children under 5 years old residing in the municipality of Guanambi-Ba, between the period from 2016 to 2020, regarding the characteristics of the individual and the causes of death. Methodology: This is a cross-sectional study, using the sex ratio at birth and mortality rate in children under five as indicators. Data were acquired through SIM (Mortality Information System) and SINASC (Live Birth Information System). Results: A total of 89 deaths were recorded in children under five years of age in the municipality of Guanambi-Ba in the years 2016 to 2020, with higher frequencies for males in all years surveyed. It was noticed that in the years 2019 and 2020 there was a decrease in the difference in deaths between the sexes, with a considerable increase in female deaths and a drop in male deaths compared to 2018. Between 1 to 4 complete years the causes of death change in characteristics compared to the neonatal phase. Conclusion: It can be concluded that in the municipality of Guanambi-Ba, between the years 2016 to 2020 there was no stable trend in the MMR5, but a constant variation between the years. Therefore, this study is relevant with regard to the management of health care for pregnant women and children.